Road Edge Parking Management Strategy in Semarang City: Collaborative Governance Perspective - Maya Rumantir; Hardi Warsono; Budi Puspo Priyadi; Retno Sunu Astuti; Teuku Afrizal (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2021)
Roadside parking makes a large contribution to local revenue if managed properly. However, in its implementation, there have been many practices of "illegal parking" which have made the management very bad and caused losses to the parking users. Thus, government collaboration in parking management is important to involve all relevant stakeholders involved as a whole, forming cooperation, both in consensus and in decision making. This study focuses on-street parking management strategy from a collaborative governance perspective. This study used a descriptive qualitative method with the research location in the city of Semarang. Data collection was carried out through in-depth interviews with related agencies, apart from observing and documenting. From observations in the field, the researchers found that the Semarang City Government has not performed its function optimally as the main pillar in determining policies related to parking management. For this reason, a management strategy with a government collaboration concept approach that involves several stakeholders is needed to solve the parking problem collectively. With the concept of collaborative governance, it will reduce irregularities and monopolies in the implementation of parking management.